2015
DOI: 10.1016/j.molmet.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Fructose ingestion acutely stimulates circulating FGF21 levels in humans

Abstract: ObjectiveFibroblast growth factor 21 (FGF21) is a hormone with pleiotropic metabolic activities which, in rodents, is robustly regulated by fasting and ketogenic diets. In contrast, similar dietary interventions have either no or minimal effects on circulating FGF21 in humans. Moreover, no intervention or dietary challenge has been shown to acutely stimulate circulating FGF21 in either humans or animals. Recent animal data suggest that the transcription factor Carbohydrate Responsive-Element Binding Protein (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
198
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 199 publications
(219 citation statements)
references
References 45 publications
20
198
1
Order By: Relevance
“…While the induction of FGF21 in this human study required the fairly dramatic stimulus of prolonged and complete calorie abstinence, other studies have found evidence for FGF21 release in response to more narrow nutritional interventions, such as with acute carbohydrate administration (44) or prolonged protein restriction (45). A limitation of this study is the fact that we were not able to explore all of the potential physiologic functions of FGF21 during fasting, including its effects on growth hormone resistance and the reproductive axis, areas which may be more easily explored in longer-term fasting studies.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…While the induction of FGF21 in this human study required the fairly dramatic stimulus of prolonged and complete calorie abstinence, other studies have found evidence for FGF21 release in response to more narrow nutritional interventions, such as with acute carbohydrate administration (44) or prolonged protein restriction (45). A limitation of this study is the fact that we were not able to explore all of the potential physiologic functions of FGF21 during fasting, including its effects on growth hormone resistance and the reproductive axis, areas which may be more easily explored in longer-term fasting studies.…”
Section: Discussionmentioning
confidence: 64%
“…Importantly, the late increase in FGF21 levels in humans correlated with weight loss and markers of tissue stress, providing a rationale to focus future mechanistic studies on the role of FGF21 in regulating fuel production and trafficking during the latter phase of starvation, with a particular focus on human studies, given the apparent evolutionary divergence in some FGF21 functions between mice and humans. With regard to the potential therapeutic implications of this study, we cannot assume that any hypothesized functional roles of FGF21 in the starved state are relevant to supraphysiologic administration of FGF21 mimetics in patients with metabolic disease; however, this study underscores the emerging concept that the nutritional state has profound implications not only for the production of FGF21 (44,45), but also for its functional activity in target tissues.…”
Section: Mouse Studiesmentioning
confidence: 86%
“…In particular, we found that circulating FGF21 levels seem to be markedly induced in the fed state, within hours following ingestion of a protein-diluted meal. Interestingly, fructose or glucose ingestion rapidly induced FGF21 in humans (35), suggesting that FGF21 levels may in fact be highly responsive to nutrient balance following meal ingestion. Nevertheless, despite the induction by DPD being roughly similar, serum FGF21 levels were markedly lower in humans compared with mice.…”
Section: Resultsmentioning
confidence: 99%
“…Increased circulating FGF21 is associated with cardiometabolic risk factors including obesity, NAFLD, type 2 diabetes, and insulin resistance (179)(180)(181). FGF21 is a ChREBP transcriptional target (182), and fructose ingestion acutely and robustly induces circulating FGF21, whereas the response to glucose ingestion is less substantial and is delayed (175). Fructose-induced, circulating FGF21 may protect the liver from fructose-induced metabolic disease (183).…”
Section: Fructose Effects On Appetite and Adipositymentioning
confidence: 99%